Transforming systems of consumption and production for achieving the sustainable development goals: moving beyond efficiency - Bengtsson, Magnus; Alfredsson, Eva; Cohen, Maurie; Lorek, Sylvia; Schroeder, Patrick (Sustainability science, 2018)
The United Nations formulated the sustainable development goals (SDGs) in 2015 as a comprehensive global policy framework for addressing the most pressing social and environmental challenges currently facing humanity. In this paper, we analyse SDG 12, which aims to “ensure sustainable consumption and production patterns.” Despite long-standing political recognition of this objective, and ample scientific evidence both on its importance and on the efficacy of various ways of promoting it, the SDGs do not provide clear goals or effective guidance on how to accomplish this urgently needed transformation. Drawing from the growing body of research on sustainable consumption and production (SCP), the paper identifies two dominant vantage points—one focused on promoting more efficient production methods and products (mainly through technological improvement and informed consumer choice) and the other stressing the need to consider also overall volumes of consumption, distributional issues, and related social and institutional changes. We label these two approaches efficiency and systemic. Research shows that while the efficiency approach contains essential elements of a transition to sustainability, it is by itself highly unlikely to bring about sustainable outcomes. Concomitantly, research also finds that volumes of consumption and production are closely associated with environmental impacts, indicating a need to curtail these volumes in ways that safeguard social sustainability, which is unlikely to be possible without a restructuring of existing socioeconomic arrangements. Analysing how these two perspectives are reflected in the SDGs framework, we find that in its current conception, it mainly relies on the efficiency approach. On the basis of this assessment, we conclude that the SDGs represent a partial and inadequate conceptualisation of SCP which will hamper implementation. Based on this determination, this paper provides some suggestions on how governments and other actors involved in SDGs operationalisation could more effectively pursue SCP from a systemic standpoint and use the transformation of systems of consumption and production as a lever for achieving multiple sustainability objectives.